Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÑÐºÐ¾Ñ€Ð¾ÑÑ‚Ð¸ Ð¾Ñ…Ð»Ð°Ð¶Ð´ÐµÐ½Ð¸Ñ Ð² Ñ€Ð°Ð·Ð»Ð¸Ñ‡Ð½Ñ‹Ñ… Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð½Ñ‹Ñ… Ð¸Ð½Ñ‚ÐµÑ€Ð²Ð°Ð»Ð°Ñ… Ð½Ð° ÑÐ¾Ñ…Ñ€Ð°Ð½Ð½Ð¾ÑÑ‚ÑŒ ÑÑ‚ÐµÑ€Ð¾Ð¸Ð´Ð¾Ð³ÐµÐ½Ð½Ð¾Ð³Ð¾ Ð¿Ð¾Ñ‚ÐµÐ½Ñ†Ð¸Ð°Ð»Ð° ÑÑƒÑÐ¿ÐµÐ½Ð·Ð¸Ð¸ Ð¸Ð½Ñ‚ÐµÑ€ÑÑ‚Ð¸Ñ†Ð¸Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº ÑÐµÐ¼ÐµÐ½Ð½Ð¸ÐºÐ¾Ð² Ð²Ð·Ñ€Ð¾ÑÐ»Ñ‹Ñ… ÐºÑ€Ñ‹Ñ - Gurina, T. M.; Pakhomov, A. V.; Bozhok, G. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
The effect of cryopreservation conditions (cryoprotectant concentration, cell incubation with cryoprotectants prior to freezing, cooling of samples with various temperature intervals) on survival of steroidogenic cells in the testscular interstitium cell suspension (ICS) has been investigated. This resulted in designing of cryopreservation protocol for ICS, which provided the highest survival and functional activity of steroidogenic cells if compared with the protocols already existing for testicular biological material.